ОСНОВНІ ЕТАПИ РОЗВИТКУ ВИЩОЇ ПЕДАГОГІЧНОЇ ОСВІТИ В УКРАЇНІ (Педагогіка вищої та середньої школи, 2009)
There are the seven general stages of developing High Pedagogical Education in Ukraine in this article. They are: bearing of native High Education becoming of pedagogical education; search for contain, forms and methods of building of new High Education for different ways of state power; formation and intensive training of national pedagogical staff, assertion of system of indivisible pedagogical education in conditions of united centralization, unification of its contain, forms and methods for renovating of High pedagogical education; renew of national High Education on the democratic basis in Ukraine as in independent state.